Partial description of plasmid content in bacteria Serratia marcescens isolated locally - Khalid Ahmed; Hayfaa Alyas (College of Education for Pure Sciences, 2007)
This study involved isolation oftwenty eight primary isolates of the genus Serratia from different clinical human infections from different hospitals in Mosul city . After microscopic examination and diagnosis using biochemical tests, cultural characters and API 20 E system ,eleven isolates of Serratia marcescens were identified from them .Amplification of plasmid DNA content in S.marcescens isolates were tested in presence of chloramphenicol (1 OO}l/ml), tetracycline and starvation . The isolates showed variation in their ability to amplify their plasmid DNA content in the presence of chloramphenicol and by starvation as compared with unamplfied cultmes. While in presence of tetracycline (150 )1/ml) only one isolate out of seven showed this characteristic. Phages isolated from sewage water were used to control viabiLity of bacterial isolates. The results showed that these phages appear to be ineffective on these isolates.